Metamaterial inspired dielectric resonator MIMO antenna for isolation enhancement and linear to circular polarization of waves. (September 2021) - Dwivedi, Ajay Kumar; Sharma, Anand; Singh, Ashutosh Kumar; Singh, Vivek
Highlights: In the proposed work, two-dimensional metasurface is suspended over the MIMO DRA. Designed metasurface is used to convert LP wave to CP waves. Same metasurface is used to enhance the isolation between the antenna elements. Abstract: In this communication, a novel dielectric resonator-based multiple-input-multiple- output antenna with a metasurface module (Meta-MIMO) is investigated and analyzed. Dielectric resonator antenna is excited through a rectangular aperture and creates HEM11δ mode inside the ceramic. The salient features of the proposed configuration are: (a) metasurface module converts the linear polarized waves into circularly polarized waves; (b) suspended metasurface improves the isolation value between the antenna ports. It is verified from the measured results that the proposed antenna operates well over the 3.8–4.2 GHz frequency range. Different diversity parameters are within the desired limit, which confirms it as an efficient MIMO radiator.